Influence of flax fibers on epoxide-amine composites: Energetics of interphase formation. (21st July 2022) - Canavy, Nandy; Rouilly, Antoine; Drouet, Christophe; Thouron, Carole; Aufray, Maëlenn
Abstract: Flax fibers are particularly relevant in composite fabrication due to natural availability and mechanical properties close to glass fibers. We explore flax fiber-containing epoxy-amine (DGEBA/DETA) polymers with wide industrial applicability. Flax fibers impact the glass transition temperature (DSC), with a T g drop of 67 °C at 30 wt% loading. For deeper insight, we develop here an original mixing calorimetry approach to follow in situ DGEBA/fibers and DETA/fibers interphases. DGEBA does not interact quantitatively with flax fibers while DETA/fibers interaction is significantly exothermic and directly related to fibers content. DETA/water interaction only accounts for 25% of total heat effect. Experiments run by contacting DETA with each of the main components of flax fibers (cellulose, hemicelluloses, lignin) point out systematic exothermic effects. Considering their mean proportion in flax fibers, the sum of enthalpy contributions agrees well with the overall effect measured with entire fibers. The main contribution (58%) arises from cellulose. XRD analyses and literature considerations allow concluding on the direct implication of DETA molecules with cellulose chains, resulting in T g decrease. This work clarifies the chemical role of flax fibers in DGEBA/DETA thermosets, down to the molecular-scale, and highlights that mixing calorimetry is a powerful tool to follow interphase formation in situ . Graphical abstract: We develop a mixing calorimetry approach to follow in situ interphase formation between flax fibers and DGEBA or DETA. DETA/fibers interaction is particularly exothermic. Each component of flax fibers leads to exothermic effects, cellulose giving the most prominent enthalpy contribution. DETA interacts with cellulosic chains, which limits the amount of "reactive" amino functions for polymerization and decreases the T g value. Image 1 Highlights: Addition of flax fibers in epoxy-amine mixture leads to Tg decrease (67 characters) . Mixing microcalorimetry does not show interaction between DGEBA and flax fibers (84 characters) . DETA/fibers interaction is significantly exothermic (63 characters). Cellulose, hemicellulose, lignin and water reacted exothermically with DETA (76 characters) . Cellulose is responsible for 58% of the heat effect despite its crystallized state (83 characters).